IMPLEMENTATION OF THE TEAMS GAMES TOURNAMENT TYPE COOPERATIVE LEARNING MODEL ASSISTED WITH QUIZWHIZZER TO IMPROVE STUDENTS' COGNITIVE LEARNING OUTCOMES - Rati Rahayu; Syahril Rahayu; Fakhruddin Z (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2024)
Student learning outcomes are still relatively low because the learning model applied in schools is still focused on teacher explanations. Therefore, researchers conducted research by applying a learning model that focuses on students, namely the Teams Games Tournament (TGT) learning model. This research aims to describe the cognitive learning outcomes of MTsS Miftahul Ulum eighth-grade students after the use of a TGT-type cooperative learning technique on the foundational aviation curriculum using Quizwhizzer. This kind of research employs a quasi-experiment with a posttest-only control design. Twenty multiple-choice questions from a posttest served as the data gathering tool. Both descriptive and inferential analysis were used to examine the data. The descriptive analysis's findings demonstrate that pupils in VIII 3 have superior cognitive learning outcomes than those in VIII 1. This is evident from the fact that the control class's average score is 70.31 and the class VIII 3 students' average score is 80.47. The independent sample t-test has a significance value of 0.000, or less than 0.05, according to the inferential analysis findings. Thus, based on the findings of these two analyses, it can be said that students in classes VIII 3 and VIII 1 and VIII 3 who performed better after applying the Teams Games Tournament learning model to basic airplane material had very different cognitive learning outcomes.